Microbial ecology of extreme environments - Chénard, Caroline; Lauro, Federico M. (Springer, 2017)
This book explores microbial lifestyles, biochemical adaptations, and trophic interactions occurring in extreme environments. By summarizing the latest findings in the field it provides a valuable reference for future studies. Spark ideas for biotechnological and commercial exploitation of microbiomes at the extremes of life are presented. Chapters on viruses complement this highly informative book. In a vertical journey through the microbial biosphere it covers aspects of cold environments, hot environments, extreme saline environments, and extreme pressure environments, and more. From the deep sea, through polar deserts, up to the clouds in the air - the diversity of microbial life in all habitats is described, explored, and comprehensively reviewed. Possible biotechnical applications are discussed. This book aims to provide a useful reference for those who want to start a research program in extreme microbiology and, hopefully, inspire new research directions.
Keywords: Extreme environments -- Microbiology.; elektronické knihy; electronic books